Investigation of frequency and risk factors for restenosis after carotid endarterectomy - Arnautović, Bojana; Končar, Igor (Medicinski podmladak, 2022)
Introduction: Carotid artery restenosis (CR) is a  significant long-term comlication of carotid endarterectomy (CEA). CR is the result of neointimal hyperplasia in the early postoperative period or recurrent atherosclerotic lesions in the following period. Numerous studies have incriminated several risk factors as predisposing conditions for CR.The definite role of each predisposing factor, however, is still widely debated.Aim: Investigation of frequency and risk factors for restenosis after carotid endarterectomy.Material and methods: We  reviewed the data of 295 patients who underwent CEA between 2008-2010.  Postoperative duplex studies were performed on control examinations in following period beteween 2011-2019. Retrospective analysis was performed to assess the effect  of demographic, clinical and laboratory characteristics of patients on the development of restenosis after CEA.Results: Restenosis occurred in 76 (26%) patients after CEA, with the highest incidence during the third (33%) and fourth (25%) year of follow-up. Patients with diabetes (p = 0.048) and peripheral arterial occlusive disease (PAOD) (p = 0.041) had significant statistical correlation with the occurrence of restenosis, as well as parameters of lipid status - cholesterol values (p = 0.025), serum low-density lipoprptein (LDL) (p = 0.036) and non high-density lipoprotein (non-HDL) (p = 0.041).Conclusion: The results of our study confirm the significant role of atherosclerotic risk factors in the development of CR in the later postoperative period. More frequent monitoring and control of systemic risk factors in these patients is necessary in order to prevent the development of CR.Keywords: carotid restenosis, cartotid endarterectomy, risk factors
Keywords: carotid restenosis, cartotid endarterectomy, risk factors